2023
DOI: 10.1002/ccr3.7830
|View full text |Cite
|
Sign up to set email alerts
|

Alpha‐gal syndrome—Food or drug allergy: A case report

Marina Božan,
Vesna Vukičević Lazarević,
Ivan Marković
et al.

Abstract: Key Clinical MessageAlpha‐gal syndrome is an immunoglobulin E‐mediated hypersensitivity characterized by delayed allergic reactions to ingested products containing alpha‐gal carbohydrate. We present a patient with recurrent urticaria and suspected repaglinide hypersensitivity, who was eventually diagnosed with alpha‐gal syndrome, wanting to emphasize possible drug allergy misdiagnosis and required caution with the medication choice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
(119 reference statements)
0
1
0
Order By: Relevance
“…5 Ixodes ricinus, the castor bean tick, is the most widespread tick species in Europe and has been reported to contain alpha-gal in the midgut. 6 In previous studies, patients with alpha-gal syndrome reported a higher proportion of allergic reactions following insect stings and were more likely to be sensitized to honey bee and wasp or fire ant than patients without this allergy. 7 Increased levels of alpha-gal IgE were described following Hymenoptera sting.…”
Section: Introductionmentioning
confidence: 94%
“…5 Ixodes ricinus, the castor bean tick, is the most widespread tick species in Europe and has been reported to contain alpha-gal in the midgut. 6 In previous studies, patients with alpha-gal syndrome reported a higher proportion of allergic reactions following insect stings and were more likely to be sensitized to honey bee and wasp or fire ant than patients without this allergy. 7 Increased levels of alpha-gal IgE were described following Hymenoptera sting.…”
Section: Introductionmentioning
confidence: 94%